HEAT WAVES IN CENTRAL REGIONS OF UKRAINE UNDER THE CONDITIONS OF CLIMATE CHANGE - Сніжко, С.; Шевченко, О.; Свінціцька, Г. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2018)
On the basis of 10 selected stations of the meteorological network heat wave episodes for Сentral regions of Ukraine in the summer months June to August in 1961–2015 have been identified. Duration, intensity and temporal variability of heat wave cases are analyzed. It is proved that the heat wave observed at the end of July – the first part of August 2010 was the longest and the most intense nearly for all stations of the Central regions of Ukraine during the research period. Keywords: heat wave, heat wave duration, heat wave intensity, climate change.